Some 2-Amino-benzo[de]isoquinolin-1,3-diones as Antimicrobial Agents - Al-Salahi1, R.A.; Marzouk1, M.S. (Asian Journal of Chemistry, 2014)
A new series of 2-amino-benzo[de]isoquinolin-1,3-diones was evaluated in vitro for their antimicrobial activity. The tested compounds were investigated against a variety of species of Gram negative bacteria (E. coli RCMB 010052 and Pseudomonas aeroginosa RCMB 010043) and Gram positive bacteria (Bacillis subtilis RCMB 010067 and Streptococcus pneumoniae RCMB 010010). Furthermore, they were screened against several types of fungi as Syncephalastrum racemosum (RCMB 05922), Aspergillus fumigatus (RCMB 02568), Candida albicans (RCMB 05036) and Geotricum candidum (RCMB 05097). The minimum inhibitory concentration (MIC) of the tested molecules was determined using broth double dilution method (Serially diluted technique) in proper nutrient. The findings revealed that compounds 1, 3, 7, 10, 12, 13, 14 and 16 have shown as potential antimicrobial agents and could be useful as corner stones for further development to design more potent antimicrobial agents.